Ultrafast time-resolved photoelectron spectroscopy of solvated systems. (August 2015) - Jordan, Inga; Huppert, Martin; Hartweg, Sebastian; Wörner, Hans Jakob
Synopsis: Photoionization delays reveal electron dynamics on ultrashort time scales. Here, we present attosecond time-resolved experimental results of gas-phase and liquid water and we discuss the analysis methods to retrieve molecular ionization delays therefrom.